Analysis of Seawater Quality in the Villa Ombak Gili Terawangan Area, Pemenang District - Nurhidayah, Nurhidayah; Sholehah, Hijriati; Nurhidayatullah, Nurhidayatullah; Mulhidin, Mulhidin; Azwaruddin, Azwaruddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Tourism is one of the most rapidly growing sectors globally and plays a vital role in regional development by contributing to foreign exchange earnings, job creation, and poverty alleviation. Gili Trawangan, a small island in West Lombok, is a popular marine tourism destination experiencing rapid growth in tourist visits and supporting infrastructure, such as hotels and restaurants. This growth has led to increased population density and higher environmental pressures, particularly in the form of liquid waste and pollutants entering coastal waters. If not properly managed, these pollutants can degrade water quality and marine ecosystems. This study aims to assess the quality of seawater in the Villa Ombak area of Gili Trawangan, located in Pemenang District. A quantitative research method was applied, with seawater samples collected from six stations using the Niskin bottle method at a depth of one meter. Parameters analyzed included physical (temperature, total suspended solids/TSS), chemical (pH, salinity, dissolved oxygen/DO, ammonia-N/NH₃-N, nitrate-N/NO₃-N, phosphate/PO₄, oil and fat), and biological (total and faecal coliform) characteristics. Laboratory analysis was conducted at the Mataram PUPR Laboratory, and results were compared to the Indonesian Government Regulation (PP) No. 22 of 2021 on seawater quality standards. The findings showed that all measured parameters met the required quality standards for marine tourism and biota. Recorded values included a temperature of 29°C, TSS 2.5 mg/L, pH 8.2, salinity 33 PSU, DO 6.9 mg/L, NH₃-N 0.019 mg/L, NO₃-N 0.0017 mg/L, oil and fat <0.03 mg/L, total coliform 185 MPN/100 mL, and faecal coliform 0 MPN/100 mL. Although still within safe limits, ongoing monitoring and environmental management are essential to prevent ecological degradation and to ensure the sustainability of marine tourism in the area.